2003
DOI: 10.1507/endocrj.50.379
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Mild Hyperthyrotropinemia after Discontinuation of Three-Year Course of Low-Dose L-Thyroxine Therapy in Infants with Borderline Hypothyroidism

Abstract: Abstract. Treatment plan for neonates with borderline hypothyroidism (persistent hyperthyrotropinemia with normothyroxinemia) has not been established. In this study, changes in thyroid function after discontinuation of low-dose L-thyroxine (L-T4) supplement in infants with the condition were evaluated. Fourteen infants with hyperthyrotropinemia at neonatal screening had repeated hyperthyrotropinemia (>8 mU/L) with normothyroxinemia. TSH response was exaggerated at TRH testing. The subjects were treated with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 13 publications
2
32
0
2
Order By: Relevance
“…Over 40% of the HT patients in our study were eventually normalized their FT 4 (i.e. had t‐HT), which is in partial agreement with some studies 3,26 and in contrast to others 4,5 . In a longitudinal study of thyroid function in 44 children with mild HT at neonatal screening, Leonardi et al.…”
Section: Discussionsupporting
confidence: 86%
“…Over 40% of the HT patients in our study were eventually normalized their FT 4 (i.e. had t‐HT), which is in partial agreement with some studies 3,26 and in contrast to others 4,5 . In a longitudinal study of thyroid function in 44 children with mild HT at neonatal screening, Leonardi et al.…”
Section: Discussionsupporting
confidence: 86%
“…During the follow-up, we observed that low-dose l-T4, (2-5 lg/kg/day) was sufficient for treatment. Although there is no satisfactory knowledge in the literature about the dose of l-T4 to be used in hyperthyrotropinaemia, low dose l-T4 was used, similar to our study, in babies with borderline hypothyroidism (15,16). Our patients were followed up at 8 weeks intervals due to the risk of hyperthyroidism.…”
Section: Discussionmentioning
confidence: 59%
“…Literature on MNH is sparse, with few studies reporting outcomes on small numbers of patients . The natural history of this condition is not well defined, and published results are contradictory regarding the percentage of patients requiring permanent replacement …”
Section: Introductionmentioning
confidence: 99%